Relatório técnico jogos eletrônicos, autismo e mediação: sobre as possibilidades de um encontro. - Souza, Shyrlane do Nascimento (2023)
This research aims to discuss the issues of autism and mediation, based on the experience of building an electronic game for so-called autistic people. The initial project called TECA (Educational Technology for autistic children) was started in 2019 at the institution APAE (Association of Parents and Friends of the Exceptional) in the municipality of Sobral - CE, which offers ultidisciplinary care for people with Intellectual Disability, Multiple Disorders, of Neurodevelopment and Genetic Syndromes. In the face of successful experiences, the project continues to expand, currently through the theme of music, with the game Rock You Music: Musical game for autistic children. The research method was divided into the following stages: Development Stage, where researchers created the contents of the activities, stages, levels, functions and accessibility features of the game, according to the interest of children and adolescents diagnosed with autism who participated in the search. After the Sessions Stage, which was organized by the APAE psychologist, the children and adolescents had access to the material. Then, data collection instruments were used, such as EGameFlow and the Content Validity Index (CVI), applied with family members and then with the institution's multidisciplinary team, respectively.The instruments were selected through a partnership between Computer Engineering and Psychology, which are the areas of knowledge that guide this work. To improve the research, clinical cases are presented, based on the use of the game with the participants, who are people aged between 8 and 14 years old, attending at APAE. The team of researchers is composed of a psychologist from APAE, a graduate student and supervisor of the master's degree in Computer Engineering and supervisor of the master's degree in Psychology and Public Policy, both at the Federal University of Ceará - Campus de Sobral. It is concluded that the material can enable the expansion of interaction, bricolage and subjective expression of the participants. It is expected that the project will help its target audience (so-called autistic people, families, professionals) to use their capacities for invention and creativity, as they are fundamental in building the mediation between the child and the Other